Myeloperoxidase is not a good biomarker for preeclampsia prediction - Rocha-Penha, L. [UNESP]; Bettiol, H.; Barbieri, M. A.; Cardoso, V. C.; Cavalli, R. C.; Sandrim, V. C. [UNESP] (Springer Nature, 2017)
Myeloperoxidase is a proinflammatory enzyme found to be increased in patients with established preeclampsia but never investigated before the disease onset. Here we examined myeloperoxidase concentration and activity in plasma and urine samples from pregnant women who remained normotensive throughout pregnancy and those who developed preeclampsia in order to assess its potential to predict this disorder. Our sample consisted of 30 cases who developed preeclampsia (14 severe and 16 mild) and 57 controls who remained healthy throughout pregnancy, derived from the Brazilian Ribeirão Preto and São Luís prenatal cohort (BRISA). Myeloperoxidase concentration were assessed using a commercial ELISA kit and enzymatic activity through tetramethylbenzidine oxidation. No statistical differences were found in myeloperoxidase levels nor activity between plasma or urine samples from controls, severe and mild cases. Myeloperoxidase did not seem to have a potential application for preeclampsia prediction.